Polydopamine@carbon nanotube reinforced and calcium sulphoaluminate coated hydrogels encapsulating bacterial spores for self-healing cementitious composites - Feng, Jianhang (2023)
Bacterial spores have been applied to develop self-healing cementitious composites, while protections of endospores in concrete are required. Herein, one reinforced calcium alginate hydrogel with a protective shell was designed to encapsulate bacterial spores. The hydrogels were reinforced by highly dispersed carbon nanotubes (CNTs) coated with polydopamine, which led to more spherical shaped hydrogels, hence calcium sulphoaluminate (CSA) cement can be uniformly coated on the hydrogels to form the protective shell. With the reinforcement of CNTs and the coating of CSA cement, the hydrogels were conducive to germination, growth and activities of bacteria even after the hydrogels endured long-term exposure to strongly alkaline and calcium concentrated solution. Due to these positive effects of the modified hydrogels on spores, concrete with spores encapsulated in the modified hydrogels obtained enhanced self-healing performance in terms of crack width and permeability reductions as more biological mediated calcium carbonate was precipitated within cracks.